Ordinances of the City of Norfolk, with the Amended Charter and an Appendix, at 60, ch. 8, § 1 (1894). - (:unkn) unknown (General Publisher, 1894)
If any person carry about his person, hid from common observation, any pistol, dirk, bowie-knife, razor, slung-shot, or any weapon of the like kind, he shall be fined not less than twenty nor more than one hundred dollars, and such pistol, dirk, bowie knife, razor, slungshot, or any weapon of the like kind, may be seized by an officer
--
Keywords: CARRY - CONCEALED